Environment-friendly flame-retardant leather material as well as preparation method and application thereof
By using raw materials and molding processes with specific ratios, environmentally friendly flame-retardant leather materials with excellent flame retardant, wear-resistant and weather-resistant stability are prepared, solving the problem of difficult coordination of performance of existing leather materials.
Patent Information
- Application Number
- CN202411558775.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
The existing leather materials have poor flame retardant performance and poor wear resistance, and are difficult to coordinately improve flame retardant and wear resistance, and the product's weather resistance stability is also poor.
Eco-friendly flame retardant leather materials are prepared through extrusion and calendering processes using raw materials including pvc resin powder, calcium powder, flat-adjuvant additives, magnesium hydroxide flame retardant, glass fiber modifier, oleic acid amide, euco-oxide phenol, silicone oil and calcium stearate.
The flame retardant, wear resistance and weather stability of leather materials are significantly improved, and the product performance is coordinated and optimized.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leather materials, and in particular to an environmentally friendly flame-retardant leather material and a preparation method and application thereof. Background Art
[0002] Leather is animal skin that has been denatured and not easy to rot after physical and chemical processes such as dehairing and tanning. Leather is composed of natural protein fibers tightly woven in three-dimensional space. Its surface has a special grain layer with natural grain and luster and feels comfortable.
[0003] The existing leather materials have poor flame retardancy and poor wear resistance. It is difficult to coordinate and improve the flame retardancy and wear resistance of the products. In addition, the weathering stability of the products is poor, which further limits the use efficiency of the products. Based on this, the present invention further improves them. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an environmentally friendly flame-retardant leather material and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides an environmentally friendly flame-retardant leather material, comprising the following raw materials in parts by weight: 45-50 parts of PVC resin powder, 10-15 parts of calcium powder, 6-10 parts of leveling additives, 5-8 parts of magnesium hydroxide flame retardant, 4-7 parts of glass fiber modifier, 2-5 parts of oleic acid amide, 2-4 parts of eugenol, 2-3 parts of silicone oil, and 2-5 parts of calcium stearate.
[0006] Preferably, the preparation method of the leveling additive is: S11: Mix the nano-mica powder in a sufficient amount of sulfuric acid solution, and then wash, filter and dry; S12: Preparation of calcined alumina agent: The alumina is calcined at 210-220°C for 20 minutes, then cooled to 55°C at a rate of 1-3°C / min, kept warm, and the alumina is mixed with a sufficient amount of lanthanum nitrate solution to obtain a calcined alumina agent; S13: 5-8 parts of S11 dried nano-mica powder, 1-3 parts of silane coupling agent, 2-5 parts of calcined alumina agent and 6-10 parts of 2-5% by mass sodium lignin sulfonate solution are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a leveling additive.
[0007] Preferably, the mass fraction of the sulfuric acid solution is 2-5%; the mass fraction of the lanthanum nitrate solution is 3-6%.
[0008] Preferably, the silane coupling agent is silane coupling agent KH550.
[0009] Preferably, the preparation method of the glass fiber modifier is: S101: immersing the glass fiber in a sufficient amount of sodium silicate solution and subjecting it to ultrasonic treatment, filtering and drying after the immersion is completed to obtain a glass fiber agent; S102: 2-5 parts of glass fiber agent, 1-3 parts of lanthanum chloride solution, 2-5 parts of barium carbonate and 4-7 parts of chitosan solution are mixed and stirred, and after the stirring is completed, the mixture is filtered and dried to obtain a glass fiber modifier.
[0010] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.
[0011] Preferably, the mass fraction of the chitosan solution is 2-5%.
[0012] Preferably, the ultrasonic power of the immersion ultrasonic treatment is 350-400 W, and the ultrasonic time is 20-30 min.
[0013] Preferably, the stirring speed of the blending and stirring process is 450-550 r / min, and the stirring time is 20-30 min.
[0014] The present invention also provides a method for preparing an environmentally friendly flame-retardant leather material, comprising the following steps: The raw materials were weighed according to weight, extruded in an extruder at a temperature of 210° C., calendered at a temperature of 200° C., and finally cooled to room temperature to obtain an environmentally friendly flame-retardant leather material.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The environmentally friendly flame-retardant leather material of the present invention adopts PVC resin powder in combination with functional additives such as oleic acid amide, eugenol, silicone oil, etc., and optimizes the flame retardancy of the product by adding the flame retardant. The leveling additive and the glass fiber modifier are added at the same time to coordinate and cooperate with each other, and the wear resistance and flame retardancy of the product are improved, and the weathering stability of the product is significantly improved; the leveling additive adopts nano mica powder as a lamella structure, is treated with an acid solution to optimize its active efficiency, and then is mixed with a silane coupling agent and a sodium lignin sulfonate solution with a mass fraction of 2-5% of a calcined alumina agent and ball milled to achieve a good effect. The raw materials are coordinated and matched to enhance the interface between the raw materials. At the same time, the calcined alumina agent is treated with alumina calcination, optimized with lanthanum nitrate solution, and coordinated with nano-mica powder to improve the coordination of system performance and optimize the weathering stability of the product. The glass fiber modifier is treated with sodium silicate solution, and then mixed and stirred with lanthanum chloride solution, barium carbonate and chitosan solution. Through the coordination and blending of the raw materials, the obtained glass fiber modifier can better cooperate with the leveling additives, and the performance of the product is further improved. DETAILED DESCRIPTION
[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The environmentally friendly flame-retardant leather material of this embodiment includes the following raw materials in parts by weight: 45-50 parts of PVC resin powder, 10-15 parts of calcium powder, 6-10 parts of leveling additives, 5-8 parts of magnesium hydroxide flame retardant, 4-7 parts of glass fiber modifier, 2-5 parts of oleic acid amide, 2-4 parts of eugenol, 2-3 parts of silicone oil, and 2-5 parts of calcium stearate.
[0018] The preparation method of the leveling additive of this embodiment is: S11: Mix the nano-mica powder in a sufficient amount of sulfuric acid solution, and then wash, filter and dry. S12: Preparation of calcined alumina agent: The alumina is calcined at 210-220°C for 20 minutes, then cooled to 55°C at a rate of 1-3°C / min, kept warm, and the alumina is mixed with a sufficient amount of lanthanum nitrate solution to obtain a calcined alumina agent; S13: 5-8 parts of S11 dried nano-mica powder, 1-3 parts of silane coupling agent, 2-5 parts of calcined alumina agent and 6-10 parts of 2-5% by mass sodium lignin sulfonate solution are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a leveling additive.
[0019] The mass fraction of the sulfuric acid solution in this embodiment is 2-5%; the mass fraction of the lanthanum nitrate solution is 3-6%.
[0020] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0021] The preparation method of the glass fiber modifier of this embodiment is: S101: immersing the glass fiber in a sufficient amount of sodium silicate solution and subjecting it to ultrasonic treatment, filtering and drying after the immersion is completed to obtain a glass fiber agent; S102: 2-5 parts of glass fiber agent, 1-3 parts of lanthanum chloride solution, 2-5 parts of barium carbonate and 4-7 parts of chitosan solution are mixed and stirred, and after the stirring is completed, the mixture is filtered and dried to obtain a glass fiber modifier.
[0022] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.
[0023] The mass fraction of the chitosan solution in this embodiment is 2-5%.
[0024] The ultrasonic power of the immersion ultrasonic treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min.
[0025] The stirring speed of the blending and stirring process in this embodiment is 450-550r / min, and the stirring time is 20-30min.
[0026] The method for preparing an environmentally friendly flame-retardant leather material of this embodiment comprises the following steps: The raw materials were weighed according to weight, extruded in an extruder at a temperature of 210° C., calendered at a temperature of 200° C., and finally cooled to room temperature to obtain an environmentally friendly flame-retardant leather material.
[0027] Example 1. The environmentally friendly flame-retardant leather material of this embodiment includes the following raw materials in parts by weight: 45 parts of PVC resin powder, 10 parts of calcium powder, 6 parts of leveling additives, 5 parts of magnesium hydroxide flame retardant, 4 parts of glass fiber modifier, 2 parts of oleamide, 2 parts of eugenol, 2 parts of silicone oil, and 2 parts of calcium stearate.
[0028] The preparation method of the leveling additive of this embodiment is: S11: Mix the nano-mica powder in a sufficient amount of sulfuric acid solution, and then wash, filter and dry; S12: Preparation of calcined alumina agent: The alumina is calcined at 210°C for 20 minutes, then cooled to 55°C at a rate of 1°C / min, kept warm, and the alumina is mixed with a sufficient amount of lanthanum nitrate solution to obtain a calcined alumina agent; S13: 5 parts of S11 dried nano-mica powder, 1 part of silane coupling agent, 2 parts of calcined alumina agent and 6 parts of 2% by mass sodium lignin sulfonate solution are blended and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a leveling additive.
[0029] The mass fraction of the sulfuric acid solution in this embodiment is 2%; the mass fraction of the lanthanum nitrate solution is 3%.
[0030] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0031] The preparation method of the glass fiber modifier of this embodiment is: S101: immersing the glass fiber in a sufficient amount of sodium silicate solution and subjecting it to ultrasonic treatment, filtering and drying after the immersion is completed to obtain a glass fiber agent; S102: 2 parts of glass fiber agent, 1 part of lanthanum chloride solution, 2 parts of barium carbonate and 4 parts of chitosan solution are mixed and stirred, and after the stirring is completed, the mixture is filtered and dried to obtain a glass fiber modifier.
[0032] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 4%.
[0033] The mass fraction of the chitosan solution in this embodiment is 2%.
[0034] The ultrasonic power of the immersion ultrasonic treatment in this embodiment is 350W, and the ultrasonic time is 20min.
[0035] The stirring speed of the blending and stirring process in this embodiment is 450 r / min, and the stirring time is 20 min.
[0036] The method for preparing an environmentally friendly flame-retardant leather material of this embodiment comprises the following steps: The raw materials were weighed according to weight, extruded in an extruder at a temperature of 210° C., calendered at a temperature of 200° C., and finally cooled to room temperature to obtain an environmentally friendly flame-retardant leather material.
[0037] Example 2. The environmentally friendly flame-retardant leather material of this embodiment includes the following raw materials in parts by weight: 50 parts of PVC resin powder, 15 parts of calcium powder, 10 parts of leveling additives, 8 parts of magnesium hydroxide flame retardant, 7 parts of glass fiber modifier, 5 parts of oleamide, 4 parts of eugenol, 3 parts of silicone oil, and 5 parts of calcium stearate.
[0038] The preparation method of the leveling additive of this embodiment is: S11: Mix the nano-mica powder in a sufficient amount of sulfuric acid solution, and then wash, filter and dry; S12: Preparation of calcined alumina agent: The alumina is calcined at 220°C for 20 minutes, then cooled to 55°C at a rate of 3°C / min, kept warm, and the alumina is mixed with a sufficient amount of lanthanum nitrate solution to obtain a calcined alumina agent; S13: 8 parts of S11 dried nano-mica powder, 3 parts of silane coupling agent, 5 parts of calcined alumina agent and 10 parts of 5% by mass sodium lignin sulfonate solution are blended and ball-milled at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a leveling additive.
[0039] The mass fraction of the sulfuric acid solution in this embodiment is 5%; the mass fraction of the lanthanum nitrate solution is 6%.
[0040] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0041] The preparation method of the glass fiber modifier of this embodiment is: S101: immersing the glass fiber in a sufficient amount of sodium silicate solution and subjecting it to ultrasonic treatment, filtering and drying after the immersion is completed to obtain a glass fiber agent; S102: 5 parts of glass fiber agent, 3 parts of lanthanum chloride solution, 5 parts of barium carbonate and 7 parts of chitosan solution are mixed and stirred, and after the stirring is completed, the mixture is filtered and dried to obtain a glass fiber modifier.
[0042] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 7%.
[0043] The mass fraction of the chitosan solution in this embodiment is 5%.
[0044] The ultrasonic power of the immersion ultrasonic treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.
[0045] The stirring speed of the blending and stirring process in this embodiment is 550r / min, and the stirring time is 30min.
[0046] The method for preparing an environmentally friendly flame-retardant leather material of this embodiment comprises the following steps: The raw materials were weighed according to weight, extruded in an extruder at a temperature of 210° C., calendered at a temperature of 200° C., and finally cooled to room temperature to obtain an environmentally friendly flame-retardant leather material.
[0047] Example 3. The environmentally friendly flame-retardant leather material of this embodiment includes the following raw materials in parts by weight: 47 parts of PVC resin powder, 12.5 parts of calcium powder, 8 parts of leveling additives, 6.5 parts of magnesium hydroxide flame retardant, 5.5 parts of glass fiber modifier, 3.5 parts of oleic acid amide, 3 parts of eugenol, 2.5 parts of silicone oil, and 3.5 parts of calcium stearate.
[0048] The preparation method of the leveling additive of this embodiment is: S11: Mix the nano-mica powder in a sufficient amount of sulfuric acid solution, and then wash, filter and dry; S12: Preparation of calcined alumina agent: The alumina is calcined at 215°C for 20 minutes, then cooled to 55°C at a rate of 2°C / min, kept warm, and the alumina is mixed with a sufficient amount of lanthanum nitrate solution to obtain a calcined alumina agent; S13: 6.5 parts of S11 dried nano-mica powder, 2 parts of silane coupling agent, 3.5 parts of calcined alumina agent and 8 parts of 2-5% by mass sodium lignin sulfonate solution are mixed and ball-milled at a ball-milling speed of 1250 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a leveling additive.
[0049] The mass fraction of the sulfuric acid solution in this embodiment is 3.5%; the mass fraction of the lanthanum nitrate solution is 4.5%.
[0050] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0051] The preparation method of the glass fiber modifier of this embodiment is: S101: immersing the glass fiber in a sufficient amount of sodium silicate solution and subjecting it to ultrasonic treatment, filtering and drying after the immersion is completed to obtain a glass fiber agent; S102: 3.5 parts of glass fiber agent, 2 parts of lanthanum chloride solution, 3.5 parts of barium carbonate and 5.5 parts of chitosan solution are mixed and stirred, and after stirring, the mixture is filtered and dried to obtain a glass fiber modifier.
[0052] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 5.5%.
[0053] The mass fraction of the chitosan solution in this embodiment is 3.5%.
[0054] The ultrasonic power of the immersion ultrasonic treatment in this embodiment is 370W, and the ultrasonic time is 25min.
[0055] The stirring speed of the blending and stirring process in this embodiment is 500 r / min, and the stirring time is 25 min.
[0056] The method for preparing an environmentally friendly flame-retardant leather material of this embodiment comprises the following steps: The raw materials were weighed according to weight, extruded in an extruder at a temperature of 210° C., calendered at a temperature of 200° C., and finally cooled to room temperature to obtain an environmentally friendly flame-retardant leather material.
[0057] Comparative Example 1. The difference from Example 3 is that no leveling additive is added.
[0058] Comparative Example 2. The difference from Example 3 is that no calcined alumina agent is added in the preparation of the leveling additive.
[0059] Comparative Example 3. The difference from Example 3 is that the calcined alumina agent is directly replaced by alumina raw material.
[0060] Comparative Example 4. The difference from Example 3 is that the S11 dried nano mica powder is not added in the preparation of the leveling additive.
[0061] Comparative Example 5. The difference from Example 3 is that no glass fiber modifier is added.
[0062] Comparative Example 6. The difference from Example 3 is that no lanthanum chloride solution and barium carbonate are added in the preparation of the glass fiber modifier.
[0063] Comparative Example 7. The difference from Example 3 is that no glass fiber agent is added in the preparation of the glass fiber modifier.
[0064] The product performance of Examples 1-3 and Comparative Examples 1-7 was tested. The products were aged for 720 hours under UV conditions with a UV intensity of 10 mW / cm2. The tests were as follows:
[0065] It can be seen from comparative examples 1-7 and embodiment 3 that the product of embodiment 3 has excellent flame retardancy and wear resistance, and the product has significant performance stability under weathering conditions; If neither the leveling additive nor the glass fiber modifier is added to the product, the performance of the product will deteriorate significantly. The synergistic effect of the two additives will be the most obvious. When no calcined alumina agent is added in the preparation of the leveling additive, the calcined alumina agent is directly replaced by alumina raw material, and the nano mica powder dried by S11 is not added in the preparation of the leveling additive, the performance of the product tends to deteriorate. In particular, when no nano mica powder dried by S11 is added in the preparation of the leveling additive, the performance stability of the product under weathering conditions deteriorates significantly. At the same time, when no lanthanum chloride solution, barium carbonate, or glass fiber agent is added in the preparation of the glass fiber modifier, the performance of the product tends to deteriorate. Only when the product raw material is obtained by the method of the present invention, the product performance effect is the most significant, and the effects of other methods are not as obvious as those of the present invention.
[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0067] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An environmentally friendly flame-retardant leather material, characterized in that: It includes the following raw materials in parts by weight: 45-50 parts of PVC resin powder, 10-15 parts of calcium powder, 6-10 parts of leveling additives, 5-8 parts of magnesium hydroxide flame retardant, 4-7 parts of glass fiber modifier, 2-5 parts of oleic acid amide, 2-4 parts of eugenol, 2-3 parts of silicone oil, and 2-5 parts of calcium stearate.
2. The environmentally friendly flame-retardant leather material according to claim 1, characterized in that: The preparation method of the leveling additive is as follows: S11: Mix the nano-mica powder in a sufficient amount of sulfuric acid solution, and then wash, filter and dry; S12: Preparation of calcined alumina agent: The alumina is calcined at 210-220°C for 20 minutes, then cooled to 55°C at a rate of 1-3°C / min, kept warm, and the alumina is mixed with a sufficient amount of lanthanum nitrate solution to obtain a calcined alumina agent; S13: 5-8 parts of S11 dried nano-mica powder, 1-3 parts of silane coupling agent, 2-5 parts of calcined alumina agent and 6-10 parts of 2-5% by mass sodium lignin sulfonate solution are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a leveling additive.
3. The environmentally friendly flame-retardant leather material according to claim 2, characterized in that: The mass fraction of the sulfuric acid solution is 2-5%; the mass fraction of the lanthanum nitrate solution is 3-6%.
4. The environmentally friendly flame-retardant leather material according to claim 2, characterized in that: The silane coupling agent is silane coupling agent KH550.
5. The environmentally friendly flame-retardant leather material according to claim 1, characterized in that: The preparation method of the glass fiber modifier is: S101: immersing the glass fiber in a sufficient amount of sodium silicate solution and subjecting it to ultrasonic treatment, filtering and drying after the immersion is completed to obtain a glass fiber agent; S102: 2-5 parts of glass fiber agent, 1-3 parts of lanthanum chloride solution, 2-5 parts of barium carbonate and 4-7 parts of chitosan solution are mixed and stirred, and after the stirring is completed, the mixture is filtered and dried to obtain a glass fiber modifier.
6. The environmentally friendly flame-retardant leather material according to claim 5, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.
7. The environmentally friendly flame-retardant leather material according to claim 5, characterized in that: The mass fraction of the chitosan solution is 2-5%.
8. The environmentally friendly flame-retardant leather material according to claim 5, characterized in that: The ultrasonic power of the immersion ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
9. The environmentally friendly flame-retardant leather material according to claim 5, characterized in that: The stirring speed of the blending and stirring process is 450-550r / min, and the stirring time is 20-30min.
10. A method for preparing the environmentally friendly flame-retardant leather material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials were weighed according to weight, extruded in an extruder at a temperature of 210° C., calendered at a temperature of 200° C., and finally cooled to room temperature to obtain an environmentally friendly flame-retardant leather material.
Citation Information
Cited By
PVC foaming material, PVC artificial leather, preparation method and application thereof
CN120424454A